Behçet’s Disease: An Account of Three Cases - Paudyal, B; Gyawalee, M; Manandhar, A; Sigdel, K (Journal of Nepal Health Research Council, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Behçet’s disease is a chronic relapsing inflammatory condition affecting multiple organ-systems of the body. Patient’s with this disease present to different specialists with wide spectrum of clinical features of varying severity. Worldwide, this disease is clustered around certain parts of Asia, previously known as ‘Silk route’. Here we present three cases of Behçet’s disease who presented to our clinic with ocular, dermatological, and articular manifestations. <span style="font-size: 11.0pt; line-height: 115%; font-family: ";Calibri";,";sans-serif";; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ";Times New Roman";; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Keywords: arthritis; Behçet’s disease; genital ulcers; ocular inflammation; oral ulcers<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>